Humanizing Online Learning: The Role of AI+XR-Based Virtual Tutors in Adaptive Education - Cardoso, Alexandre; Siqueira, Alexandre Gomes de; Martins, Valéria Farinazzo; Oliveira Neto, João Soares de; Eliseo, Maria Amelia; Silveira, Ismar Frango (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2025: Anais do XXII Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2025.16483, 2025)
The integration of Artificial Intelligence (AI) and Extended Reality (XR) in education has opened new possibilities for adaptive and personalized learning. Among these, Virtual Humans (VH), which are AI-driven XR avatars capable of real-time humanized interaction, have emerged as promising tools for content adaptation, emotional support, and learner engagement. This paper examines the roles of VH in fostering adaptive learning, emphasizing their capability to meet diverse learner needs through responsive, individualized content adaptations, based on a literature review. This study investigates the effectiveness of a VH-based system, VirtualTutor, developed to enhance online learning in a Computer Science course. A case study involving 265 undergraduate students evaluated the impact of the system on engagement, perceived usefulness, and comprehension. The results of this study are presented in this paper. Findings support the potential of VH to foster inclusive, scalable, and learner-centered educational environments, while also identifying key areas for system refinement and future research.